New infestation records of two-spotted spider mites on potato tubers under storage conditions and response of genotypes at Kulumsa, Ethiopia - Tilahun, Gizaw Wegayehu; Gure, Tamirat Negash (International Journal of Agricultural Research, Innovation and Technology, 2024)
The study sought to ascertain spider mite prevalence, infestation, and identification and to assess the response of potato genotypes. In 2022, this pest was only observed on some genotypes in December. In late January, an infestation, incidence, and severity increased from 10 to 13 genotypes on potato tuber stocks stored for irrigation experiments. Those genotypes were planted in irrigated fields, and the sprouted tuber losses ranged from 12.5% to 100% and up to 15.38% in the 2022 and 2023 records, respectively. Following this, spider mites, often known as two-spotted spider mites (TSSM) or Tetranychus urticae, were identified. This is the first time a potato sprout infestation has been recorded in Ethiopia. The two-spotted spider mites damaged the tubers quantitatively by sucking the moisture of sprouts up to the 5th grade, with 97 and >75% infestation levels, incidence, and severity, respectively. The pest grows very rapidly and hastens the drying of sprouted tuber leaves. Some genotypes were resistant to TSSM and recovered after the sprouts were infected and dried, which were treated with pesticides in 2023. The typical agricultural insecticides were ineffective in controlling the pest in the first year, and a Profenofos was applied in the second year. Thus, seed tubers are the main production limit unless appropriate research efforts are undertaken and management techniques are created. Int. J. Agril. Res. Innov. Tech. 13(2): 55-63, Dec 2023